High-resolution UVES/VLT spectra of white dwarfs observed for the ESO SN Ia Progenitor Survey III. DA white dwarfs - Koester, D.; Voss, B.; Napiwotzki, R.; Christlieb, Norbert; Homeier, Derek; Lisker, T.; Reimers, D.; Heber, Ulrich (Astronomy & Astrophysics, 2009)
Context. The ESO Supernova Ia Progenitor Survey (SPY) took high-resolution spectra of more than 1000 white dwarfs and pre-white dwarfs. About two thirds of the stars observed are hydrogen-dominated DA white dwarfs. Here we present a catalog and detailed spectroscopic analysis of the DA stars in the SPY.Aims. Atmospheric parameters effective temperature and surface gravity are determined for normal DAs. Double-degenerate binaries, DAs with magnetic fields or dM companions, are classified and discussed.Methods. The spectra are compared with theoretical model atmospheres using a chi(2) fitting technique.Results. Our final sample contains 615 DAs, which show only hydrogen features in their spectra, although some are double-degenerate binaries. 187 are new detections or classifications. We also find 10 magnetic DAs (4 new) and 46 DA+dM pairs (10 new).
Keywords: stars: white dwarfs